The Impact of Live Streaming and Influencer Marketing on Consumer Purchase Decisions on TikTok Shop - Andreanto, Deo; Muhammad Reihan Maulana; Misbak (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
The TikTok Shop platform is one example of how the advancement of digital technology has altered how consumers shop. Influencer marketing and live streaming are two increasingly common marketing techniques for drawing customers. The purpose of this study is to examine how TikTok Shop users' decisions to buy are impacted by live streaming and influencer marketing features. 95 respondents who regularly used TikTok Shop were surveyed as part of the quantitative research methodology. In addition to testing for normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, F test, and T test to examine the relationships between variables, validity and reliability tests were performed to guarantee the quality of the data. The findings demonstrated that, with a regression coefficient value of 0.306 and a significant level of 0.000, the live streaming feature significantly influenced purchasing decisions. Influencer marketing, on the other hand, has a higher impact, as indicated by its regression coefficient value of 0.713 and significance level of 0.000. Also, the regression analysis revealed that, with an Adjusted R Square value of 0.852, both factors concurrently affected the choice to buy. Influencer marketing combined with live streaming features is therefore crucial for enhancing customer purchasing decisions. These findings illustrate that TikTok Shop’s success is not just about technology or features, but also about how influencing trust, community engagement, and live streaming create a unique, highly engaging shopping environment that drives both impulse and repeat purchases across generations. This study investigates the impact of live streaming and influences marketing features on consumer purchase decisions on TikTok Shop can also be the alternative marketing media. Also, the results of this research show that the influence of live streaming promotions and influences can have a significant positive impact on a person's purchasing decisions on an e-commerce platform.